The whiteness of lighting and colour preference, Part 2: A meta-analysis of psychophysical data. (January 2020) - Huang, Z; Liu, Q; Luo, MR; Pointer, MR; Wu, B; Liu, A
In this work, the correlation between the perceived whiteness of lighting and the corresponding colour preference of observers was comprehensively investigated based on the data of 19 groups of experiments collected from 14 studies. The dataset included 13 experiments with constant correlated colour temperature and 6 experiments with multiple correlated colour temperatures, with illuminance levels ranging from 200 lx to 500 lx. For the five studies implemented by the authors, the subjective ratings of colour preference and the whiteness of lighting were acquired. For other cases, only the preference ratings were collected while the whiteness of lighting was quantified by a measure named degree of neutrality ( Sneutral ), which has been validated in our previous work. The meta-analysis results confirm our former statement that people prefer whiter illumination and further specify its prerequisite. That is, the whiteness of lighting generally correlates well with colour preference under the conditions where the candidate lights differed to a certain extent in white. In addition, it was further demonstrated that for the scenarios with multiple correlated colour temperatures ranging from 2500 K to 5500 K people indeed preferred perceptually whiter light chromaticities, while for correlated colour temperatures higher than 5500 K it seemed that they appeared too cold to be preferred.